REVITALISASI KUNINGAN MOJOKERTO: DIVERSIFIKASI PRODUK MELALUI TRANSFORMASI LOKALITAS MENUJU MODERNITAS - Ira Audia Agustina; Ida Bagus Ananta Wijaya (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2020)
The brass craftsmen form Bejijong Village, Trowulan Subistrict , Mojokerto Regency, is a craftsmen community who had a heyday in Majapahit Era (1293-1500) and still operating until today. But now its existence are in stagnation due to the difficulty of getting the successor and weak competitiveness to the evolution of  lifestyle and market tastes. The products produced by Bejijong craftsmen are limited to souvenir products, which resulting a very narrow-range market penetration. In international market, Bejijong craftmen’s product have a low product diversification compared to products from India and Thailand which have a similar qualities and product characteristics. Some of these problems make the Bejijong craftsmen’s products are difficult to compete in domestic and international market. Therefore, this research was held to contributing the diversification development of products that can be produced by Bejijong craftsmen, namely as a variety of interior functional products. This study uses the design thinking brainstorming with the use of transformative design method, and material combining, to creating a product novelty and market-price competitiveness. Data collection was obtained through literature studies on the richness locality and originality of Mojokerto’s motifs, shapes and patterns, as well as market research about consumer’s tastes and needs by field observations, conducting interviews as well as questionnaries with the Bejijong craftsmen communities and customers. Through this method, Mojokerto’s richness of local shape, motifs, and pattern will be applied to a variety of aesthetically-interior functional products that can address current market needs. It is hoped that by this product transformation can escalating the product competitiveness and offering the uniqueness of locality and identity to the Bejijong craftmen’s products